Source for Gloxinia (Sinningia Spp.) and Potato (Solanum Tuberosum) Micropropagation - Duong Tan Nhut; Mai Thi Ngoc Huong (ASEAN Journal on Science and Technology for Development, 2006)
An efficient lighting system (Compact 3U) was successfully applied to the micropropagation of gloxinia and potato plants. To compare the in vitro growth of plantlets under Neon and Compact 3U lighting systems, gloxinia and potato shoots were cultured on suitable media at different light intensities: (1) 45 µmol m-2s-1 (under Neon lighting system as a control); (2) 45 µmol m-2s-1, (3) 60µmol m-2s-1, and (4) 75 µmol m-2s-1 (under Compact 3U lighting systems). The results obtained after 3 weeks of in vitro culture and 6 weeks of acclimatization in a greenhouse showed that the growth of plantlets cultured under the Compact 3U system was better than that under Neon lighting system. The Compact 3U lighting source had a highly significant effect on the growth and development of gloxinia and potato plantlets. Besides, the data in our study also indicated that gloxinia and potato plantlets adapted differently to different lighting sources and light intensities.